German Verbal-Nominal Phrases (stehen, stellen, schließen, fassen + Nomen) through the Prism of Conceptual Schemes - A. S. Nozdrina (Научный диалог)
The article deals with the fixed verb combinations of the German language from the point of view of cognitive linguistics. As the material under study, fixed verb combinations are presented, built according to the type “verb + (preposition) + noun”. The author dwells on four German verbs (stehen, stellen, schließen, fassen) and possible combinations with them. The examples under consideration are combined into groups where different nouns are used with one verb, usually of an abstract nature. An attempt is made to analyze conceptual schemes that model fragments of the surrounding reality and to identify the images that the carrier of the German linguistic culture operates with. The study of the figurative component of fixed verb combinations allows us to classify them on conceptual grounds, namely to single out the metaphor “container” and the spatial metaphor. The author also dwells on the conceptual metaphor of objectification. Particular attention is paid not only to the semantics of individual components of verbal phrases (verb, preposition and noun), but also to the grammatical characteristics of lexemes. The analysis performed makes it possible to speak about the presence in the German linguistic culture of basic universal concepts, designed in the form of conceptual schemes. The studied conceptual schemes make it possible to clearly demonstrate the thesis that abstract phenomena are often comprehended through concrete-sensory images.